Long COVID symptoms in exposed and infected children, adolescents and their parents one year after SARS-CoV-2 infection: A prospective observational cohort study - Haddad, Anneke; Janda, Ales̆; Renk, Hanna; Stich, Maximilian; Frieh, Pauline; Kaier, Klaus; Lohrmann, Florens; Nieters, Alexandra; Willems, Anna; Huzly, Daniela; Dulovic, Alex; Schneiderhan-Marra, Nicole; et al. (EBioMedicine, 2022)
Long COVID in children and adolescents remains poorly understood due to a lack of well-controlled studies with long-term follow-up. In particular, the impact of the family context on persistent symptoms following SARS-CoV-2 infection remains unknown. We examined long COVID symptoms in a cohort of infected children, adolescents, and adults and their exposed but non-infected household members approximately 1 year after infection and investigated clustering of persistent symptoms within households.